The volleyball approach: An exploration of balance - Ciapponi, T. M.; McLaughlin, E. J.; Hudson, J. L (ISBS - Conference Proceedings Archive (Konstanz), 1995)
The approach is a critical component of a successful offense in volleyball. Ideally, the hitter will use the approach to achieve a high jump with minimal horizontal motion (Prsala, 1982). According to Dusault (1986), greater height in the jump is predicated on greater horizontal velocity in the approach. Evidently, the hitter should maximize horizontal velocity at touch-down and minimize it at take-off. How does the hitter arrest mobility? If mobility and stability are inversely related, can mobility be decreased through increases in stability? Do performers of distinct skill levels regulate the mobility and stability components of balance differently? The purpose of this study was to explore balance and skill in the volleyball approach and to gain insight into the preceding questions.